A novel hydraulic-mechanical hybrid transmission in tidal current turbines. (September 2015) - Liu, Hongwei; Lin, Yonggang; Shi, Maoshun; Li, Wei; Gu, Haigang; Xu, Quankun; Tu, Le
Abstract: Tidal current energy is a promising renewable energy, and it has become a research hotspot all over the world. Tidal current turbines (TCTs) are the devices that capture tidal current energy and convert it into electricity. Power train is one of the key technologies, and a gearbox is traditionally used. Because of the disadvantages of the gearbox, several soft power transmission methods have been studied, such as hydraulic power train and direct-drive train. Aiming for maximum power point tracking (MPPT) and constant frequency simultaneously, this paper introduces the hydraulic-mechanical hybrid transmission for TCT. Different from the traditional mechanical transmission, the hydraulic-mechanical hybrid transmission uses a two-degree-of-freedom planetary gear (TDPG) as the power split device. In this transmission, the rotor speed can be regulated by hydraulic pump displacement control to realize the MPPT, and the power can be stabilized through the hydraulic system. In this paper, the hydraulic-mechanical hybrid transmission is introduced, and the characteristics of the TDPG are analyzed first. Then, the control strategy of TCT is proposed. Finally, the system is modeled and constructed, and the simulation results confirm the validity of the hydraulic-mechanical hybrid transmission of TCT. Highlights: This paper has introduced a hydraulic-mechanical hybrid power transmission for tidal current turbine. The working principle and characteristic of the hybrid power train were given and compared with the mechanical power train. In order to obtain the performance of the hybrid power train, a 50 W small scale prototype adopting the hybrid power train was designed and the mathematic and simulation model of the mechanical-hydraulic hybrid transmission system were constructed. Based on this model, the control strategies of the maximum power point tracking (MPPT) and constant frequency of the TCT were presented and simulated. The results showed that the MPPT and constant frequency can be achieved simultaneously by the hydraulic-mechanical hybrid transmission without the complex electronics devices. Besides, the results showed the transmitted power can be smoothed by using the present transmission. At last, some experiments based on mechanical transmission was conducted in order to analyze the efficiency of the hybrid transmission system.